Edukasi Gizi Seimbang pada Siswa SDN 3 Picungremuk - Annida Nihayati; Rahma Aulianisa; Listia Rahmadiana; Ismi Desmia; Riva Ahmad F; Indri Ayu Widianti (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
The low understanding of nutritious food choices among elementary school children remains a problem because it impacts their health, learning abilities, and future eating habits. A similar situation was found at SDN 3 Picungremuk, where students often choose flavored foods without considering their nutritional content. This community service activity aims to improve students' nutritional knowledge through education on the concept of "Isi Piringku" (My Plate). The implementation stages include identifying needs through observation and discussions with teachers, developing materials tailored to children's development, conducting interactive socialization, and practicing how to assemble a balanced meal plate using visual media. Evaluation was carried out through pre- and post-tests accompanied by food selection simulations. The output showed a significant increase in understanding. Before the education, most students were unable to combine foods correctly. After the activity, all participants were able to assemble a meal plate according to the principles of balanced nutrition. These findings prove that the use of visual media and hands-on practice is an effective method for instilling healthy eating habits in elementary school children.